The Three Models of Emotional Intelligence and Performance in a Hot and Cool go/no-go Task in Undergraduate Students - Gutiérrez-Cobo, María J.; Cabello, Rosario; Fernández-Berrocal, Pablo (Frontiers in Behavioral Neuroscience, 2017)
Emotional intelligence (EI), or the ability to perceive, use, understand, and regulate emotions, appears to be helpful in the performance of “hot” (i.e., emotionally laden) cognitive tasks when using performance-based ability models, but not when using self-report EI models. The aim of this study is to analyze the relationship between EI (as measured through a performance-based ability test, a self-report mixed test, and a self-report ability test) and cognitive control ability during the performance of hot and “cool” (i.e., non-emotionally laden) “go/no-go” tasks. An experimental design was used for this study in which 187 undergraduate students (25% men) with a mean age of 21.93 years (standard deviation = 3.8) completed the three EI tests of interest (MSCEIT, TMMS and EQi:S) as well as go/no-go tasks using faces and geometric figures as stimuli. The results provide evidence for negative associations between the “managing” branch of EI measured through the performance-based ability test of EI and the cognitive control index of the hot go/no-go task, although similar evidence was not found when using the cool task. Further, the present study failed to observe consistent results when using the self-report EI instruments. These findings are discussed in terms of both the validity and implications of the various EI models.